Research and Design of Flood Discharge and Energy Dissipation Structures of Datengxia Hydro Project - TAN Zhijun; PAN Minghong (Renmin Zhujiang)
The design of flood discharge and energy dissipation structures is important and is the primary research problem in the layout of hydro projects,which involves the problems of discharge capacity,cavitation of flow surface,water aeration,and sediment abrasion and scouring of downstream riverbeds.For the Datengxia hydro project,its maximum discharge capacity of flood discharge structures reaches 66,200 m3/s,and the Froude number of energy dissipation structures is low.Therefore,the scheme of bottom outlets for flood discharge and surface outlets for drift discharge is adopted for flood discharge structures,and the underflow energy dissipation mode of the secondary stilling basin is adopted for energy dissipation structures.As flood discharge structures mainly adopt the bottom outlets for flood discharge,and the radial gate bears huge water thrust,the steel beam is selected as the radial gate support,which solves the difficulties in engineering design and provides a reference for similar projects.